Analisis Perlindungan Hukum Terhadap Pengguna Jasa Notaris Berdasarkan UUPK Dan Perspektif Islam - Bagas Indria Wibisono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze the legal protection for notary service users based on the Consumer Protection Act (UUPK) and Islamic perspectives. Notaries, as public officials authorized to create authentic deeds, play a crucial role in providing legal certainty to the public. However, notaries' obligations to provide clear and specific legal guidance have not been fully implemented, resulting in inadequate legal protection for service users. Within the context of UUPK, consumers have the right to receive true, clear, and honest information, as well as the right to advocacy and protection. The Islamic perspective also emphasizes the importance of justice, transparency, and consumer rights protection, including the obligation of service providers to provide accurate information and avoid harmful practices. The research method used is normative juridical with statutory and conceptual approaches. Data were collected from various legal sources, books, journals, and relevant encyclopedias. The analysis indicates that notaries need to enhance transparency and the quality of legal guidance to ensure that consumer rights are well protected. n conclusion, notaries must provide specific, clear, and thorough legal guidance to achieve effective legal protection for their service users. This aligns with the objectives of UUPK and the principles of consumer protection in Islam, aiming to create benefits for society.